BRIDGING KNOWLEDGE AND PRACTICE IN SURGICAL WOUND CARE: A CROSS-SECTIONAL STUDY AMONG NURSES AT A MALAYSIAN TERTIARY HOSPITAL - Makajil , Johari Daud; A/P Letchumikandanc, Nanthini; Hamdan, Nurain (Malaysian Journal of Public Health Medicine, 2026)
Surgical wound care is a crucial aspect of postoperative nursing. In other words, this is important for recovery, complications, and patient satisfaction. The purpose of this study was to evaluate the knowledge and practice of nurses in the surgical ward of Sabah Women and Children’s Hospital regarding surgical wound management. A cross- sectional study design was employed from July to December 2024, utilising simple random sampling to select 60 Nurses. A self-developed, validated questionnaire in English was used to collect the data. It consisted of three sections, including demographics, knowledge, and practice. The experts validated the instrument, which showed high internal consistency (Cronbach’s alpha > 0.80). The data was analysed using SPSS version 24. The analysis revealed that most respondents were female (96.7%), with a mean age of 29.4 years and an average of 7.3 years of clinical practice experience. The general average knowledge score achieved was 3.8 (SD = 0.6), based on the highest scores, indicating a strong understanding of theoretical concepts related to infection recognition and wound assessment. Nonetheless, notable gaps in knowledge were identified regarding moist wound healing and the use of topical antiseptics. The practice scores were generally high, with a mean of 4.1 and a standard deviation of 0.5. Most mothers demonstrated a high level of compliance with aseptic technique and hand hygiene. However, the use of separate tools on infected wounds was inconsistent. The results highlighted the need for ongoing clinical training, adherence to established procedures, and the implementation of regular audit mechanisms for surgical wound care. This study provides a basis for identifying and informing institutional policies and targeted nursing education.